Determination of 6258-70, a new semi-synthetic taxane, in rat plasma and tissues: Application to the pharmacokinetics and tissue distribution study - Simin Zhao; Yuanyuan Zhang; Ping Ju; Liqiang Gu; Rui Zhuang; Longshan Zhao; Xing Tang; Kaishun Bi; Xiaohui Chen (Elsevier, 2016)
Cancer is the leading cause of death all over the world. Among the chemotherapy drugs, taxanes play an important role in cancer treatment. 6258-70 is a new semi-synthetic taxane which has a broad spectrum of antitumor activity. A fast and reliable high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method was developed for quantification of 6258-70 in rat plasma and tissues in this paper. After extraction by liquid-liquid extraction method with methyl tert-butyl ether, the samples were separated on a Kinetex C18 column (50 mm×2.1 mm, 2.6 µm, Phenomenex, USA) within 3 min. The method was fully validated with the matrix effect between 87.7% and 99.5% and the recovery ranging from 80.3% to 90.1%. The intra- and inter-day precisions were less than 9.5% and the accuracy ranged from −3.8% to 6.5%. The reliable method was successfully applied to the pharmacokinetics and tissue distribution studies of 6258-70 after intravenous administration in rats. The pharmacokinetic results indicated that the pharmacokinetic behavior of 6258-70 in rats was in accordance with linear features within tested dosage of 1 to 4 mg/kg, and there was no significant difference between the two genders. The tissue distribution study showed that 6258-70 had an effective penetration, spread widely and rapidly and could cross blood-brain barrier. The results of pharmacokinetics and tissue distribution may provide a guide for future study.